2020
DOI: 10.1212/nxi.0000000000000805
|View full text |Cite
|
Sign up to set email alerts
|

Altered fovea in AQP4-IgG–seropositive neuromyelitis optica spectrum disorders

Abstract: ObjectiveTo investigate disease-specific foveal shape changes in patients with neuromyelitis optica spectrum disorders (NMOSDs) using foveal morphometry.MethodsThis cross-sectional study included macular spectral domain optical coherence tomography scans of 52 eyes from 28 patients with aquaporin-4 immunoglobulin G (AQP4-IgG)-seropositive NMOSD, 116 eyes from 60 patients with MS, and 123 eyes from 62 healthy controls (HCs), retrospectively, and an independent confirmatory cohort comprised 33/33 patients with N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 39 publications
3
37
1
Order By: Relevance
“…Although OCT has been used for the evaluation of ON in NMO or MS in many studies, longitudinal observation studies have been rare. It is reported that NMO-ON eyes have lower peri-papillary retinal nerve fiber layer and macular ganglion cell + inner plexiform layer thicknesses, as well as a “flater” disc when compared with MS-ON eyes ( 21 , 37 ). Moreover, while MS-ON mostly affected the small-diameter neurons in the temporal quadrant of the optic disc, NMO-ON more affected the nerve fibers above and below the optic disc ( 38 , 39 ), consistent with the results in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Although OCT has been used for the evaluation of ON in NMO or MS in many studies, longitudinal observation studies have been rare. It is reported that NMO-ON eyes have lower peri-papillary retinal nerve fiber layer and macular ganglion cell + inner plexiform layer thicknesses, as well as a “flater” disc when compared with MS-ON eyes ( 21 , 37 ). Moreover, while MS-ON mostly affected the small-diameter neurons in the temporal quadrant of the optic disc, NMO-ON more affected the nerve fibers above and below the optic disc ( 38 , 39 ), consistent with the results in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In the central nervous system (CNS), the water channel AQP4, involved in the processes of osmoregulation, is highly expressed on astrocytic end‐feet (forming part of the blood–brain barrier) and ventricular ependyma (Mader, Brimberg, & Diamond, 2017; Rosales & Kister, 2016; Wingerchuk, Lennon, Pittock, Lucchinetti, & Weinshenker, 2006). ⁠ Importantly, also Müller cells of the retina express this membrane protein, what can lead to alter fovea shape in AQP4‐IgG(+) patients (Motamedi et al., 2020; Yamamura & Nakashima, 2017). Moreover, AQP4 is widespread in many organs outside CNS, such as kidneys, placenta, stomach, skeletal muscle, lungs, the inner ear, lacrimal and salivary glands, and olfactory epithelial cells (Rosales & Kister, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…and ventricular ependyma (Mader, Brimberg, & Diamond, 2017;Rosales & Kister, 2016;. Importantly, also Müller cells of the retina express this membrane protein, what can lead to alter fovea shape in AQP4-IgG(+) patients (Motamedi et al, 2020;Yamamura & Nakashima, 2017). Moreover, AQP4 is widespread in many organs outside CNS, such as kidneys, placenta, stomach, skeletal muscle, lungs, the inner ear, lacrimal and salivary glands, and olfactory epithelial cells (Rosales & Kister, 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is accumulating evidence for subclinical tissue damage in NMOSD and MOGAD from recent MRI and retinal imaging studies with optical coherence tomography (OCT) even in the absence of clinical symptoms. 810 Microstructural brain tissue alterations, spinal cord atrophy, and loss of retinal ganglion cells without brain or spinal cord symptoms or optic neuritis attacks have been repeatedly reported which challenges the current view that tissue damage does not occur independently of relapses in these conditions. However, these findings are still too preliminary to justify routine imaging follow-up in these patients as we cannot judge whether switch of immunotherapy based solely on imaging studies would result in a better prognosis with less long-term disability.…”
mentioning
confidence: 93%